A gradient structure nickel-copper-tungsten alloy and preparation method thereof
Through electrochemical deposition technology and computer-controlled electrodeposition parameters, a gradient structure nickel-copper-tungsten ternary alloy with chemical composition gradient and grain size gradient was prepared, which solved the problem that nickel-copper-tungsten alloys in the prior art was difficult to prepare gradient structures, achieved synergistic improvement of multiple properties, and broadened the application range of nickel-based alloys.
Patent Information
- Application Number
- CN202211517119.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-11-29
AI Technical Summary
The prior art is difficult to prepare a gradient structure in nickel-copper-tungsten ternary alloys, and the existing gradient structure metal nickel or nickel-tungsten alloys have single performance, and the space for regulation is limited, which cannot meet the needs of high conductivity, high corrosion resistance and high hardness.
Using electrochemical deposition technology, a gradient structure nickel copper-tungsten ternary alloy with chemical composition gradient and grain size gradient was prepared by computer-controlled electrodeposition parameters. Additives such as copper salt, tungstate, citric acid or citrate, and sodium saccharin are used to regulate the concentration and current density of the electroplating solution to achieve precise control of the gradient structure.
The gradient structure preparation of nickel-copper-tungsten alloy has been achieved, and the synergistic improvement of multiple properties such as conductivity, corrosion resistance and wear resistance can meet the needs of high-performance electrical contacts and other materials, and broaden the application range of nickel-based alloys.
Smart Images

Figure CN115726010B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and in particular relates to a gradient structure nickel-copper-tungsten alloy and a preparation method thereof. Background Art
[0002] The microstructure, composition or atomic structure of gradient structure materials presents a gradient distribution in space and is commonly found in nature. At present, in response to the demand for new metal materials, gradient structures have been widely introduced into their design and development in order to achieve excellent performance in terms of conductivity, corrosion resistance, and wear resistance of gradient structure materials. Among the preparation technologies for gradient structured metal materials that have been developed, the size of gradient structured materials by electrodeposition is almost unrestricted and has high controllability, and is widely used in the preparation technology of gradient structured metal materials.
[0003] The Chinese patent with announcement number CN111254467B discloses a gradient structure nickel-tungsten alloy, a preparation method and a new layered structure, which relate to the field of metal material technology. The preparation method provided by the invention utilizes electrochemical deposition technology, and by computer-controlled electrodeposition parameters, a grain size gradient with a gradual transition from micron-scale coarse crystals to nanocrystals and a composition gradient with a gradually increasing tungsten content can be prepared in the nickel-tungsten alloy in different distribution forms. This is conducive to regulating the comprehensive performance of the overall material in a larger scale space, thereby avoiding the shortcomings of poor plasticity / toughness of homogeneous nanostructures. The gradient structure nickel-tungsten alloy prepared by the above method can further broaden the application scope of nickel-tungsten alloys and provide technical reserves for future engineering applications. The new layered structure includes a substrate and a gradient structure nickel-tungsten alloy coating. The Chinese patent with announcement number CN104862748B discloses a low-cost, more industrially tractable gradient metal nickel and its preparation method. It is prepared by electroplating method, with nickel as the consumable anode. According to different microstructure or mechanical property requirements, the current density and additive concentration are controlled by computer over time, and the grain size gradient metal nickel is deposited under the action of direct current. The size of this gradient structure metal nickel is almost unlimited, the gradient distribution form is controllable, the grain size gradually increases from 10-100nm to 1-30μm, and there is no interface between the structural parts of each level; the gradient structure metal nickel has excellent mechanical properties, its yield strength is ≥750MPa, which is 3-4 times that of traditional coarse grains, and the tensile plastic deformation reaches more than 10%, and the overall sample density is ≥99.5%. However, the products prepared by the above patents are gradient structure nickel or gradient structure nickel-tungsten alloy, not the preparation and control of gradient structure ternary alloy, the performance is single, and the space for regulation is limited. Summary of the invention
[0004] In order to overcome the above-mentioned defects, the object of the present invention is to provide a gradient structure nickel-copper-tungsten alloy and a preparation method thereof.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A preparation method of a gradient structure nickel-copper-tungsten alloy adopts electrochemical deposition technology, with nickel as a consumable anode and titanium, copper, copper alloy, steel or nickel as a cathode. A computer is used to control the change of current density and concentration of additives in the electroplating solution over time, and a gradient structure nickel-copper-tungsten ternary alloy having both a chemical composition gradient and a grain size gradient is deposited under the action of direct current; the additives include copper salt, tungstate, citric acid or citrate, and saccharin sodium.
[0007] Preferably, the current density is 20-100 mA / cm 2 .
[0008] Preferably, the copper salt is copper sulfate, and the concentration of the copper sulfate gradually increases from 0 g / L to 2-10 g / L.
[0009] Preferably, the concentration of copper sulfate is kept constant at 0 g / L within 1-1.5 h after the start of electrochemical deposition, adjusted to 0.8-2.5 g / L within the next 2-2.5 h, then adjusted to 2-10 g / L within the next 4-4.5 h, and then kept constant within the next 0.25-0.5 h, and the deposition is terminated.
[0010] Preferably, the tungstate is sodium tungstate or ammonium tungstate, and the concentration of the tungstate increases from 0 g / L to 5-20 g / L.
[0011] Preferably, the concentration of tungstate is kept constant at 0 g / L within 1-1.5 h at the beginning of electrochemical deposition, adjusted to 2.5-10 g / L within the next 2-2.5 h, and then adjusted to 5-20 g / L within the next 4-4.5 h, and then kept constant within the next 0.25-0.5 h, and the deposition is terminated.
[0012] Preferably, the citric acid or citrate is citric acid, sodium citrate dihydrate or sodium citrate pentahydrate, and the concentration of the citric acid or citrate is increased from 0 mol / L to 0.2-0.6 mol / L.
[0013] Preferably, the concentration of the citric acid or citrate is kept constant at 0 mol / L within 1-1.5 h at the start of electrochemical deposition, adjusted to 0.1-0.2 mol / L within the next 2-2.5 h, then adjusted to 0.2-0.6 mol / L within the next 4-4.5 h, and then kept constant within the next 0.25-0.5 h, and the deposition is terminated.
[0014] Preferably, the concentration of saccharin sodium is increased from 0-5 g / L to 10-15 g / L.
[0015] Preferably, the concentration of sodium saccharin is adjusted to 0-5 g / L within 1-1.5 h after the start of electrochemical deposition, adjusted to 5-7.5 g / L within the next 2-2.5 h, and then adjusted to 10-15 g / L within the next 4-4.5 h, and then maintained unchanged within the next 0.25-0.5 h, and the deposition is terminated.
[0016] Preferably, the process further includes preparing a plating solution before electrochemical deposition, wherein the plating solution includes the following components: nickel sulfate hexahydrate at a concentration of 10-60 g / L, sodium bromide at a concentration of 10-20 g / L, boric acid at a concentration of 10-20 g / L, sodium tetraborate decahydrate at a concentration of 10-40 g / L, potassium sodium tartrate at a concentration of 2-10 g / L, and sodium dodecylbenzene sulfonate at a concentration of 0.3-0.6 g / L. The pH of the plating solution is 4.8-5.2, and the temperature of the plating solution is 50-75°C.
[0017] Preferably, the temperature adjustment process of the electroplating solution is:
[0018] Stage a: The temperature of the electroplating solution is 70-75°C within 1-1.5 hours after the start of electrochemical deposition;
[0019] Stage b: From the end of stage a to the end of deposition, the temperature of the electroplating solution is maintained at 50-56°C.
[0020] A gradient structure nickel-copper-tungsten alloy prepared by the above preparation method.
[0021] Preferably, the grain size of the nickel-copper-tungsten alloy is gradually refined from 10-20 μm to 10-40 nm.
[0022] Preferably, the mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10% respectively.
[0023] The existing methods of metal alloys with gradient structures mainly include heat treatment, plastic deformation, and electrodeposition. Heat treatment and plastic deformation form a gradient form of composition or structure on the surface of the material, while electrodeposition can form a gradient structure from the surface to the inside of the entire coating. In addition, compared with heat treatment and plastic deformation, electrodeposition can independently design the distribution of grain size and element content and can achieve precise control. Copper has good plasticity / toughness, electrical conductivity and thermal conductivity. Adding copper elements to nickel-tungsten alloys has the potential to improve the overall material's electrical conductivity, corrosion resistance, wear resistance, and plasticity. However, the standard electrode potentials of nickel, copper, and tungsten are significantly different, making it difficult to directly achieve the co-deposition of the three elements nickel, copper, and tungsten. Limited by the existing preparation process, the preparation of gradient structures has not yet been achieved in nickel-copper-tungsten ternary alloys. The prior art has prepared gradient metal nickel or gradient structure nickel-tungsten alloys, such as patents CN104862748B and CN111254467B. The comprehensive performance of metal nickel or binary nickel-tungsten alloys cannot meet the requirements of material conductivity, corrosion resistance and wear resistance in practical applications compared to ternary nickel-copper-tungsten. The performance is single and the space for regulation is limited. The prior art also discloses the preparation of gradient structure nickel-copper-phosphorus alloys, such as patents CN 107268046 B and CN115233258A. However, since phosphorus is a non-metal, its conductivity and hardness are far inferior to those of metals, resulting in poor conductivity, hardness or wear resistance, which cannot meet the actual application requirements. The present invention adopts an electrodeposition method to prepare a composition gradient with gradually changing copper content and tungsten content in nickel-copper-tungsten alloy, and the gradient distribution form is precisely controllable, eliminating the difference in the performance of each element, realizing the integration of the unique properties of each component metal in the overall material, and further expanding the application range of nickel-based alloys, as described in detail as follows:
[0024] The positive beneficial effects of the present invention are:
[0025] 1. The present invention utilizes electrochemical deposition technology and controls the electrodeposition parameters by computer, so as to prepare grain size gradients in different distribution forms, which transition from micron-sized coarse grains to ultrafine grains and then to nano-sized grains, and composition gradients in which the copper and tungsten contents gradually change, in the nickel-copper-tungsten alloy, so that the microstructure and mechanical structure of the gradient structure nickel-copper-tungsten alloy can be controlled, and the quality of the gradient structure nickel-copper-tungsten alloy is good.
[0026] 2. The present invention provides a gradient structure nickel-copper-tungsten alloy. By utilizing electrochemical deposition technology and computer-controlled electrodeposition parameters, a gradient structure nickel-copper-tungsten ternary alloy with a grain size gradient of micron-scale coarse crystal-ultrafine crystal-nano crystal transition and a composition gradient of gradually changing copper content and tungsten content is prepared. The entire coating has a gradient structure from the surface to the inside, and the corresponding gradient distribution form is precisely controllable, avoiding sudden changes in the properties of each group of metals, thereby regulating the various properties of the overall material within a larger composition and scale space. The gradient structure nickel-copper-tungsten alloy prepared by the method of the present invention has synergistically improved electrical conductivity, corrosion resistance and wear resistance, which can meet the needs of high conductivity, high corrosion resistance and high hardness of materials such as high-performance electrical contacts, further broaden the application scope of nickel-based alloys, and provide technical reserves for future engineering applications.
[0027] 3. The additives of the present invention include tungstate, copper salt, citric acid or citrate, and sodium saccharin, wherein tungstate provides tungsten element in the nickel-copper-tungsten alloy coating, copper salt provides copper element in the nickel-copper-tungsten alloy coating, and citric acid or citrate is used to complex tungstate ions, copper ions and nickel ions, thereby bringing the three ion potentials closer, so that they can be precipitated together on the cathode, and at the same time, the precipitation of impurity ions can be inhibited, and the dispersion ability and covering ability of the coating can be improved; sodium saccharin can refine the grains and optimize the internal stress of the coating. The copper salt, tungstate, citric acid or citrate, and sodium saccharin additives of the present invention are gradually dripped into the electroplating solution in the form of a solution, so that the concentration of the additives changes continuously over time, and finally ensures that the grains in the entire coating are continuously refined and have no macroscopic interface. In addition, according to the specific design of the subsequent grain size gradient structure, the specific change range rate of the additive concentration over time and the electrodeposition time can be adjusted to obtain a nickel-copper-tungsten alloy with a perfect gradient structure, and the coating quality is good, there is no obvious microcrack, and the requirements of subsequent macroscopic mechanical properties are met.
[0028] 4. The temperature of the electroplating solution of the present invention is divided into two adjustment processes. In the early stage a of deposition, the grain size of the deposited layer is relatively large, and a higher temperature of 70-75°C is set, which is beneficial to increasing the activity of the three ions, improving the dispersion ability of the solution, and increasing the conductivity of the solution; in the middle and late stages b, the temperature is lowered and the temperature of the electroplating solution is maintained at 50-56°C. Since the grain size of the deposited layer is relatively small, the deposition rate is controlled at a lower temperature, which is beneficial to obtaining a finer coating and lower internal stress. The coating quality is good, which is beneficial to fully exerting the properties of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional microstructure morphology of the gradient structure nickel-copper-tungsten alloy of Example 1 of the present invention;
[0030] Figure 2 This is a cross-sectional element distribution diagram of the gradient structure nickel-copper-tungsten alloy in Example 1 of the present invention;
[0031] Figure 3 This is a cross-sectional hardness distribution diagram of the gradient structure nickel-copper-tungsten alloy in Example 1 of the present invention;
[0032] Figure 4 This is a grain size distribution effect diagram of the gradient structure nickel-copper-tungsten alloy of Example 1 of the present invention;
[0033] Figure 5 This is a cross-sectional microstructure morphology of the gradient structure nickel-copper-tungsten alloy of Example 2 of the present invention;
[0034] Figure 6 This is a cross-sectional element distribution diagram of the gradient structure nickel-copper-tungsten alloy of Example 2 of the present invention;
[0035] Figure 7 This is a cross-sectional hardness distribution diagram of the gradient structure nickel-copper-tungsten alloy of Example 2 of the present invention;
[0036] Figure 8 This is a grain size distribution effect diagram of the gradient structure nickel-copper-tungsten alloy of Example 2 of the present invention;
[0037] Fig. 9 This is a cross-sectional microstructure morphology of the gradient structure nickel-copper-tungsten alloy of Example 3 of the present invention;
[0038] Fig.10 This is a cross-sectional element distribution diagram of the gradient structure nickel-copper-tungsten alloy of Example 3 of the present invention;
[0039] Fig.11 This is a cross-sectional hardness distribution diagram of the gradient structure nickel-copper-tungsten alloy of Example 3 of the present invention;
[0040] Fig.12 This is a grain size distribution effect diagram of the gradient structure nickel-copper-tungsten alloy in Example 3 of the present invention. DETAILED DESCRIPTION
[0041] The present invention is further described below in conjunction with some specific embodiments.
[0042] Example 1
[0043] A method for preparing a gradient structure nickel-copper-tungsten alloy comprises the following steps:
[0044] (1) A metal nickel plate with a purity of 99.6% is used as a consumable anode and a metal nickel plate is used as a cathode;
[0045] Prepare 1000mL of plating solution, which includes the following components: NiSO4·6H2O: 50g / L, NaBr: 15g / L, H3BO3: 15g / L, Na2B4O7·10H2O: 40g / L, KNaC4H 12 O 104H2O: 10g / L, C 18 H 29 NaO3S: 0.5 g / L; weigh the above chemical reagents with a balance, dissolve them in ultrapure water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, and adjust the pH value of the solution to 5.0 with a dilute sulfuric acid solution or a sodium hydroxide solution.
[0046] The temperature adjustment process of the plating solution is:
[0047] Stage a: A heating device is used to control the temperature of the plating solution to 75°C within 1 hour after the start of electrochemical deposition;
[0048] Stage b: The temperature of the plating solution is maintained at 55°C from the end of stage a to the end of deposition; the temperature in stage b is adjusted at a uniform speed.
[0049] The method also includes pre-treating the substrate (cathode) before plating, wherein the pre-treatment includes mechanical grinding and polishing and surface degreasing of the substrate (cathode). Mechanical grinding and polishing is to grind the surface of the substrate with 200#, 400# and 800# sandpaper in sequence, and mechanical grinding and polishing is used to eliminate fine unevenness, oxide scale and various macro defects on the surface of the substrate, thereby improving the flatness of the surface of the substrate, and further polishing is performed to make the surface of the substrate have a mirror gloss; surface degreasing is to clean the surface of the substrate with an organic solvent, and the organic solvent is acetone or ethanol. Surface degreasing is performed to facilitate the implementation of electroplating, and the oil stains on the surface of the substrate can be removed by utilizing the principle of similar compatibility of organic solvents.
[0050] (2) Use computer to control current density and additive concentration:
[0051] Current density: During the entire electrochemical deposition process, the current density remained constant at 30 mA / cm 2 ;
[0052] At the same time, the concentration of the additive copper sulfate was regulated: the concentration of copper sulfate was maintained at 0 g / L within 1 hour after the electrochemical deposition, and then gradually increased from 0 g / L to 0.8 g / L within 2.5 hours, and then gradually increased from 0.8 g / L to 2.5 g / L within 4 hours, and finally maintained at 2.5 g / L within 0.25 hours;
[0053] At the same time, the concentration of the additive sodium tungstate was regulated: the concentration of sodium tungstate was maintained at 0 g / L within 1 hour after the electrochemical deposition, and then gradually increased from 0 g / L to 2.5 g / L within 2 hours, and then gradually increased from 2.5 g / L to 7.5 g / L within 4 hours, and finally maintained at 7.5 g / L within 0.25 hours;
[0054] At the same time, the concentration of the additive sodium citrate dihydrate was regulated: the concentration of sodium citrate dihydrate was maintained at 0 mol / L within 1 hour after the electrochemical deposition, and then the concentration of sodium citrate dihydrate was gradually increased from 0 mol / L to 0.1 mol / L within 2 hours, and then the concentration of sodium citrate dihydrate was gradually increased from 0.1 mol / L to 0.3 mol / L within 4 hours, and finally the concentration of sodium citrate dihydrate was maintained at 0.3 mol / L within 0.25 hours;
[0055] At the same time, the concentration of the additive sodium saccharin was regulated: the concentration of sodium saccharin was kept constant at 5 g / L within 1 hour after the electrochemical deposition, and then gradually increased from 5 g / L to 7.5 g / L within 2 hours, and then gradually increased from 7.5 g / L to 10 g / L within 4 hours, and finally maintained at 10 g / L within 0.25 hours;
[0056] A gradient structure nickel-copper-tungsten alloy obtained by the preparation method has a grain size gradually refined from 10-20 μm to 10-40 nm, and the mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10%.
[0057] The cross-sectional microstructure of the gradient structure nickel-copper-tungsten alloy I prepared in this embodiment is shown in FIG. Figure 1 As shown, the grain size gradually refines from micrometer level to nanometer level, and there is no obvious macro interface. The coating quality is good without obvious micro cracks.
[0058] The cross-sectional distribution of the tungsten content and copper content of the gradient structure nickel-copper-tungsten alloy I in this embodiment is shown in FIG. Figure 2 As shown by Figure 2 It can be seen that the copper content gradually increases from 0at% to ~9at%, and the tungsten content gradually increases from 0at% to ~2at%. The contents of the two elements show an obvious gradient change trend, which meets the expected effect.
[0059] Cross-sectional hardness distribution of gradient structure nickel-copper-tungsten alloy I Figure 3 As shown in Figure 1, the hardness gradually increases from 1.7 GPa to 5.7 GPa, and then gradually decreases to 5.1 GPa, showing a gradient change trend; the corresponding grain size first gradually decreases from ~20 μm to ~20 nm, and then gradually increases to ~30 nm, as shown in Figure 1. Figure 4 As shown, the microscopic grain size shows a gradient change trend, which meets the expected effect.
[0060] Example 2
[0061] A method for preparing a gradient structure nickel-copper-tungsten alloy comprises the following steps:
[0062] (1) In this embodiment, a metal nickel plate with a purity of 99.6% is used as a consumable anode and a metal nickel plate is used as a cathode;
[0063] Prepare 1000 ml of plating solution, which includes the following components: NiSO4·6H2O: 16 g / L, NaBr: 12 g / L, H3BO3: 12 g / L, Na2B4O7·10H2O: 40 g / L, KNaC4H 12 O 10 4H2O: 10g / L, C 18 H 29 NaO3S: 0.5 g / L; weigh the above chemical reagents with a balance, dissolve them in ultrapure water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, and adjust the pH value of the solution to 4.8 with dilute sulfuric acid solution or sodium hydroxide solution.
[0064] The temperature adjustment process of the plating solution is:
[0065] Stage a: a heating device is used to control the temperature of the plating solution to 70° C. within 1 hour after the start of electrochemical deposition;
[0066] Stage b: the temperature of the plating solution is maintained at 56° C. from the end of stage a to the end of deposition; the temperature in stage b is adjusted at a uniform speed.
[0067] It also includes pre-treatment of the substrate (cathode) before plating, which includes mechanical grinding and polishing and surface degreasing of the substrate (cathode). Mechanical grinding and polishing is to use 200#, 400# and 800# sandpaper to grind the surface of the substrate in sequence, and mechanical grinding and polishing is to eliminate the fine unevenness, oxide scale and various macro defects on the surface of the substrate, thereby improving the flatness of the substrate surface, and further polishing is performed to make the substrate surface have a mirror gloss. Surface degreasing is to clean the surface of the substrate with an organic solvent, and the organic solvent is acetone or ethanol. Surface degreasing is to facilitate the implementation of electroplating, and the oil stains on the surface of the substrate can be removed by using the principle of similar compatibility of organic solvents.
[0068] (2) Use computer to control current density and additive concentration:
[0069] Current density: During the entire electrochemical deposition process, the current density remained constant at 30 mA / cm 2 ;
[0070] At the same time, the concentration of the additive copper sulfate was regulated: the concentration of copper sulfate was maintained at 0 g / L within 1 hour after the electrochemical deposition, and then the concentration of copper sulfate gradually increased from 0 g / L to 0.8 g / L within 2 hours, and then the concentration of sodium tungstate gradually increased from 0.8 g / L to 2.5 g / L within 4 hours, and finally the concentration of sodium tungstate was maintained at 2.5 g / L within 0.5 hours;
[0071] At the same time, the concentration of the additive sodium tungstate was regulated: the concentration of sodium tungstate was maintained at 0 g / L within 1.5 hours after the electrochemical deposition, and then gradually increased from 0 g / L to 2.5 g / L within 2 hours, and then gradually increased from 2.5 g / L to 7.5 g / L within 4 hours, and finally maintained at 7.5 g / L within 0.25 hours;
[0072] At the same time, the concentration of the additive sodium citrate dihydrate was regulated: the concentration of copper sulfate was maintained at 0 mol / L within 1 hour after the electrochemical deposition, and the concentration of sodium citrate dihydrate was gradually increased from 0 mol / L to 0.1 mol / L within the next 2 hours, and the concentration of sodium tungstate was gradually increased from 0.1 mol / L to 0.3 mol / L within the next 4 hours, and the concentration of sodium tungstate was maintained at 0.3 mol / L within the last 0.5 hours;
[0073] At the same time, the concentration of the additive sodium saccharin was regulated: the concentration of sodium saccharin was kept constant at 5 g / L within 1 hour after the electrochemical deposition, and then gradually increased from 5 g / L to 7.5 g / L within 2 hours, and then gradually increased from 7.5 g / L to 10 g / L within 4 hours, and finally maintained at 10 g / L within 0.5 hours;
[0074] A gradient structure nickel-copper-tungsten alloy obtained by the preparation method has a grain size gradually refined from 10-20 μm to 10-40 nm, and the mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10%.
[0075] The cross-sectional microstructure of the gradient structure nickel-copper-tungsten alloy II prepared in this embodiment is shown in FIG. Figure 5 As shown, the grain size gradually refines from micrometer level to nanometer level, and there is no obvious macro interface. The coating quality is good without obvious micro cracks.
[0076] The cross-sectional distribution of the tungsten content and copper content of the gradient structure nickel-copper-tungsten alloy II in this embodiment is shown in FIG. Figure 6 As shown by Figure 6 It can be seen that the copper content first gradually increases from 0at% to ~15at% and then decreases to ~14at%, and the tungsten content first gradually increases from 0at% to ~4at% and then gradually decreases to ~2at%. The contents of both elements show an obvious gradient change trend, meeting the expected effect.
[0077] Cross-sectional hardness distribution of gradient structure nickel-copper-tungsten alloy II Figure 7 As shown in Figure 1, the hardness first increases from 1.9 GPa to 5.7 GPa, and then gradually decreases to 4.7 GPa; the corresponding grain size first decreases from ~10 μm to ~20 nm, and then gradually increases to ~40 nm, as shown in Figure 1. Figure 8As shown, the microscopic grain size shows a gradient change trend, which meets the expected effect.
[0078] Example 3
[0079] A method for preparing a gradient structure nickel-copper-tungsten alloy comprises the following steps:
[0080] (1) In this embodiment, a metal nickel plate with a purity of 99.6% is used as a consumable anode and a metal nickel plate is used as a cathode;
[0081] Prepare 1000 ml of plating solution, which includes the following components: NiSO4·6H2O: 50 g / L, NaBr: 20 g / L, H3BO3: 10 g / L, Na2B4O7·10H2O: 20 g / L, KNaC4H 12 O 10 4H2O: 10g / L, C 18 H 29 NaO3S: 0.6 g / L; weigh the above chemical reagents with a balance, dissolve them in ultrapure water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, and adjust the pH value of the solution to 5.0 with a dilute sulfuric acid solution or a sodium hydroxide solution.
[0082] The temperature adjustment process of the plating solution is:
[0083] Stage a: a heating device is used to control the temperature of the plating solution to 72° C. within 1.5 hours after the start of electrochemical deposition;
[0084] Stage b: the temperature of the plating solution is maintained at 56° C. from the end of stage a to the end of deposition; the temperature in stage b is adjusted at a uniform speed.
[0085] The method also includes pre-treating the substrate (cathode) before plating, wherein the pre-treatment includes mechanical grinding and polishing and surface degreasing of the substrate (cathode). Mechanical grinding and polishing is to grind the surface of the substrate with 200#, 400# and 800# sandpaper in sequence, and mechanical grinding and polishing is used to eliminate fine unevenness, oxide scale and various macro defects on the surface of the substrate, thereby improving the flatness of the surface of the substrate, and further polishing is performed to make the surface of the substrate have a mirror gloss; surface degreasing is to clean the surface of the substrate with an organic solvent, and the organic solvent is acetone or ethanol. Surface degreasing is performed to facilitate the implementation of electroplating, and the oil stains on the surface of the substrate can be removed by utilizing the principle of similar compatibility of organic solvents.
[0086] (2) Use computer to control current density and additive concentration:
[0087] Current density: During the entire electrochemical deposition process, the current density remains constant at 20 mA / cm 2 ;
[0088] At the same time, the concentration of the additive copper sulfate was regulated: the concentration of copper sulfate was maintained at 0 g / L within 1 hour after the electrochemical deposition, and then the concentration of copper sulfate was gradually increased from 0 g / L to 0.8 g / L within 2 hours, and then the concentration of sodium tungstate was gradually increased from 0.8 g / L to 2 g / L within 4 hours, and finally the concentration of sodium tungstate was maintained at 2 g / L within 0.25 hours;
[0089] At the same time, the concentration of the additive sodium tungstate was regulated: the concentration of sodium tungstate was maintained at 0g / L within 1 hour after the electrochemical deposition, and then gradually increased from 0g / L to 2.5g / L within 2 hours, and then gradually increased from 2.5g / L to 5g / L within 4.5 hours, and finally maintained at 5g / L within 0.25 hours;
[0090] At the same time, the concentration of the additive sodium citrate dihydrate was regulated: the concentration of copper sulfate was maintained at 0 mol / L within 1 hour after the electrochemical deposition, and the concentration of sodium citrate dihydrate was gradually increased from 0 mol / L to 0.2 mol / L within the next 2 hours, and then the concentration of sodium tungstate was gradually increased from 0.2 mol / L to 0.5 mol / L within the next 4.5 hours, and finally the concentration of sodium tungstate was maintained at 0.5 mol / L within 0.25 hours;
[0091] At the same time, the concentration of the additive sodium saccharin was regulated: the concentration of sodium saccharin was kept constant at 5 g / L within 1 hour after the electrochemical deposition, and then gradually increased from 5 g / L to 7.5 g / L within 2 hours, and then gradually increased from 7.5 g / L to 10 g / L within 4.5 hours, and finally maintained at 10 g / L within 0.25 hours;
[0092] A gradient structure nickel-copper-tungsten alloy obtained by the preparation method has a grain size gradually refined from 10-20 μm to 10-40 nm, and the mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10%.
[0093] The gradient structure nickel-copper-tungsten alloy III prepared in this embodiment is Fig. 9 As shown, the grain size gradually refines from micron-sized columnar crystals to nano-crystalline, and there is no obvious macroscopic interface. The coating quality is good without obvious microcracks.
[0094] The cross-sectional distribution of the tungsten content and copper content of the gradient structure nickel-copper-tungsten alloy III of this embodiment is shown in FIG. Fig.10 As shown by Fig.10 It can be seen that the copper content gradually increases from 0at% to ~9at%, and the tungsten content gradually increases from 0at% to ~2at%. The contents of the two elements show an obvious gradient change trend, which meets the expected effect.
[0095] Reference for cross-sectional hardness distribution of gradient structure nickel-copper-tungsten alloy III Fig.11 As shown in Figure 2, the hardness gradually increases from 1.9 GPa to 5.1 GPa; the corresponding grain size gradually decreases from ~10 μm to ~30 nm, as shown in Figure 2. Fig.12 As shown, the microscopic grain size shows a gradient change trend, which meets the expected effect.
[0096] Example 4
[0097] A method for preparing a gradient structure nickel-copper-tungsten alloy comprises the following steps:
[0098] (1) A metal nickel plate with a purity of 99.6% is used as a consumable anode and a metal nickel plate is used as a cathode;
[0099] Prepare 1000mL of plating solution, which includes the following components: NiSO4·6H2O: 20g / L, NaBr: 10g / L, H3BO3: 20g / L, Na2B4O7·10H2O: 10g / L, KNaC4H 12 O 10 4H2O: 8g / L, C 18 H 29 NaO3S: 0.4 g / L; weigh the above chemical reagents with a balance, dissolve them in ultrapure water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, and adjust the pH value of the solution to 5.0 with a dilute sulfuric acid solution or a sodium hydroxide solution.
[0100] The temperature adjustment process of the plating solution is:
[0101] Stage a: A heating device is used to control the temperature of the plating solution to 72° C. within 1 hour after the start of electrochemical deposition;
[0102] Stage b: the temperature of the plating solution is maintained at 50° C. from the end of stage a to the end of deposition; the temperature in stage b is adjusted at a uniform speed.
[0103] The method also includes pre-treating the substrate (cathode) before plating, wherein the pre-treatment includes mechanical grinding and polishing and surface degreasing of the substrate (cathode). Mechanical grinding and polishing is to grind the surface of the substrate with 200#, 400# and 800# sandpaper in sequence, and mechanical grinding and polishing is used to eliminate fine unevenness, oxide scale and various macro defects on the surface of the substrate, thereby improving the flatness of the surface of the substrate, and further polishing is performed to make the surface of the substrate have a mirror gloss; surface degreasing is to clean the surface of the substrate with an organic solvent, and the organic solvent is acetone or ethanol. Surface degreasing is performed to facilitate the implementation of electroplating, and the oil stains on the surface of the substrate can be removed by utilizing the principle of similar compatibility of organic solvents.
[0104] (2) Use computer to control current density and additive concentration:
[0105] Current density: During the entire electrochemical deposition process, the current density was kept constant at 50 mA / cm 2 ;
[0106] At the same time, the concentration of the additive copper sulfate was regulated: the concentration of copper sulfate was maintained at 0 g / L within 1.5 hours after the start of electrochemical deposition, and then the concentration of copper sulfate was gradually increased from 0 g / L to 2 g / L within 2.5 hours, and then the concentration of copper sulfate was gradually increased from 2 g / L to 10 g / L within 4.5 hours, and finally the concentration of copper sulfate was maintained at 10 g / L within 0.25 hours;
[0107] At the same time, the concentration of the additive sodium tungstate was regulated: the concentration of sodium tungstate was maintained at 0g / L within 1 hour after the electrochemical deposition, and then gradually increased from 0g / L to 5g / L within 2.5 hours, and then gradually increased from 5g / L to 15g / L within 4 hours, and finally maintained at 15g / L within 0.25 hours;
[0108] At the same time, the concentration of the additive sodium citrate dihydrate was regulated: the concentration of sodium citrate dihydrate was maintained at 0 mol / L within 1 hour after the electrochemical deposition, and then the concentration of sodium citrate dihydrate was gradually increased from 0 mol / L to 0.1 mol / L within 2 hours, and then the concentration of sodium citrate dihydrate was gradually increased from 0.1 mol / L to 0.2 mol / L within 4 hours, and finally the concentration of sodium citrate dihydrate was maintained at 0.2 mol / L within 0.25 hours;
[0109] At the same time, the concentration of the additive sodium saccharin was regulated: the concentration of sodium saccharin was kept constant at 0 g / L within 1 hour after the electrochemical deposition, and then gradually increased from 0 g / L to 5 g / L within 2.5 hours, and then gradually increased from 5 g / L to 12 g / L within 4 hours, and finally maintained at 12 g / L within 0.25 hours;
[0110] A gradient structure nickel-copper-tungsten alloy obtained by the preparation method has a grain size gradually refined from 10-20 μm to 10-40 nm, and the mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10%.
[0111] Example 5
[0112] A method for preparing a gradient structure nickel-copper-tungsten alloy comprises the following steps:
[0113] (1) A metal nickel plate with a purity of 99.6% is used as a consumable anode and a metal nickel plate is used as a cathode;
[0114] Prepare 1000mL of plating solution, which includes the following components: NiSO4·6H2O: 60g / L, NaBr: 15g / L, H3BO3: 15g / L, Na2B4O7·10H2O: 30g / L, KNaC4H 12 O 10 4H2O: 2g / L, C 18 H 29 NaO3S: 0.5 g / L; weigh the above chemical reagents with a balance, dissolve them in ultrapure water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, and adjust the pH value of the solution to 5.2 with dilute sulfuric acid solution or sodium hydroxide solution.
[0115] The temperature adjustment process of the plating solution is:
[0116] Stage a: a heating device is used to control the temperature of the plating solution to 75° C. within 1 hour after the start of electrochemical deposition;
[0117] Stage b: the temperature of the plating solution is maintained at 55° C. from the end of stage a to the end of deposition; the temperature in stage b is adjusted at a uniform speed.
[0118] The method also includes pre-treating the substrate (cathode) before plating, wherein the pre-treatment includes mechanical grinding and polishing and surface degreasing of the substrate (cathode). Mechanical grinding and polishing is to grind the surface of the substrate with 200#, 400# and 800# sandpaper in sequence, and mechanical grinding and polishing is used to eliminate fine unevenness, oxide scale and various macro defects on the surface of the substrate, thereby improving the flatness of the surface of the substrate, and further polishing is performed to make the surface of the substrate have a mirror gloss; surface degreasing is to clean the surface of the substrate with an organic solvent, and the organic solvent is acetone or ethanol. Surface degreasing is performed to facilitate the implementation of electroplating, and the oil stains on the surface of the substrate can be removed by utilizing the principle of similar compatibility of organic solvents.
[0119] (2) Use computer to control current density and additive concentration:
[0120] Current density: During the entire electrochemical deposition process, the current density remains constant at 60mA / cm 2 ;
[0121] At the same time, the concentration of the additive copper sulfate was regulated: the concentration of copper sulfate was maintained at 0 g / L within 1.5 hours after the start of electrochemical deposition, and then the concentration of copper sulfate was gradually increased from 0 g / L to 2.5 g / L within 2 hours, and then the concentration of copper sulfate was gradually increased from 2.5 g / L to 10 g / L within 4 hours, and finally the concentration of copper sulfate was maintained at 10 g / L within 0.25 hours;
[0122] At the same time, the concentration of the additive sodium tungstate was regulated: the concentration of sodium tungstate was maintained at 0 g / L within 1 hour after the electrochemical deposition, and then gradually increased from 0 g / L to 10 g / L within 2 hours, and then gradually increased from 10 g / L to 20 g / L within 4 hours, and finally maintained at 20 g / L within 0.5 hours;
[0123] At the same time, the concentration of the additive sodium citrate dihydrate was regulated: the concentration of sodium citrate dihydrate was maintained at 0 mol / L within 1.5 hours after the electrochemical deposition, and then the concentration of sodium citrate dihydrate was gradually increased from 0 mol / L to 0.2 mol / L within 2.5 hours, and then the concentration of sodium citrate dihydrate was gradually increased from 0.2 mol / L to 0.6 mol / L within 4 hours, and finally the concentration of sodium citrate dihydrate was maintained at 0.6 mol / L within 0.25 hours;
[0124] At the same time, the concentration of the additive sodium saccharin was regulated: the concentration of sodium saccharin was kept constant at 2 g / L within 1.5 h after the electrochemical deposition, and then gradually increased from 2 g / L to 7.5 g / L within 2 h, and then gradually increased from 7.5 g / L to 15 g / L within 4 h, and finally maintained at 15 g / L within 0.25 h;
[0125] A gradient structure nickel-copper-tungsten alloy obtained by the preparation method has a grain size gradually refined from 10-20 μm to 10-40 nm, and the mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10%.
[0126] Example 6
[0127] A method for preparing a gradient structure nickel-copper-tungsten alloy comprises the following steps:
[0128] (1) A metal nickel plate with a purity of 99.6% is used as a consumable anode and a metal nickel plate is used as a cathode;
[0129] Prepare 1000mL of plating solution, which includes the following components: NiSO4·6H2O: 10g / L, NaBr: 20g / L, H3BO3: 15g / L, Na2B4O7·10H2O: 40g / L, KNaC4H 12 O 10 4H2O: 10g / L, C 18 H 29 NaO3S: 0.3 g / L; weigh the above chemical reagents with a balance, dissolve them in ultrapure water in a 1000 ml beaker, stir the solution with a magnetic stirrer until it is clear, and adjust the pH value of the solution to 5.0 with a dilute sulfuric acid solution or a sodium hydroxide solution.
[0130] The temperature adjustment process of the plating solution is:
[0131] Stage a: A heating device is used to control the temperature of the plating solution to 70°C within 1.5 hours after the start of electrochemical deposition;
[0132] Stage b: The temperature of the plating solution is maintained at 55°C from the end of stage a to the end of deposition; the temperature in stage b is adjusted at a uniform speed.
[0133] The method also includes pre-treating the substrate (cathode) before plating, wherein the pre-treatment includes mechanical grinding and polishing and surface degreasing of the substrate (cathode). Mechanical grinding and polishing is to grind the surface of the substrate with 200#, 400# and 800# sandpaper in sequence, and mechanical grinding and polishing is used to eliminate fine unevenness, oxide scale and various macro defects on the surface of the substrate, thereby improving the flatness of the surface of the substrate, and further polishing is performed to make the surface of the substrate have a mirror gloss; surface degreasing is to clean the surface of the substrate with an organic solvent, and the organic solvent is acetone or ethanol. Surface degreasing is performed to facilitate the implementation of electroplating, and the oil stains on the surface of the substrate can be removed by utilizing the principle of similar compatibility of organic solvents.
[0134] (2) Use computer to control current density and additive concentration:
[0135] Current density: During the entire electrochemical deposition process, the current density remains constant at 100mA / cm 2 ;
[0136] At the same time, the concentration of the additive copper sulfate was regulated: the concentration of copper sulfate was maintained at 0 g / L within 1 hour after the electrochemical deposition, and then the concentration of copper sulfate was gradually increased from 0 g / L to 0.8 g / L within 2 hours, and then the concentration of copper sulfate was gradually increased from 0.8 g / L to 2.5 g / L within 4 hours, and finally the concentration of copper sulfate was maintained at 2.5 g / L within 0.25 hours;
[0137] At the same time, the concentration of the additive sodium tungstate was regulated: the concentration of sodium tungstate was maintained at 0 g / L within 1.5 hours after the electrochemical deposition, and then gradually increased from 0 g / L to 2.5 g / L within 2 hours, and then gradually increased from 2.5 g / L to 5 g / L within 4.5 hours, and finally maintained at 5 g / L within 0.5 hours;
[0138] At the same time, the concentration of the additive sodium citrate dihydrate was regulated: the concentration of sodium citrate dihydrate was maintained at 0 mol / L within 1 hour after the electrochemical deposition, and then the concentration of sodium citrate dihydrate was gradually increased from 0 mol / L to 0.1 mol / L within 2.5 hours, and then the concentration of sodium citrate dihydrate was gradually increased from 0.1 mol / L to 0.3 mol / L within 4 hours, and finally the concentration of sodium citrate dihydrate was maintained at 0.3 mol / L within 0.5 hours;
[0139] At the same time, the concentration of the additive sodium saccharin was regulated: the concentration of sodium saccharin was kept constant at 5 g / L within 1.5 hours after the electrochemical deposition, and then gradually increased from 5 g / L to 7 g / L within 2 hours, and then gradually increased from 7 g / L to 10 g / L within 4 hours, and finally maintained at 10 g / L within 0.25 hours;
[0140] A gradient structure nickel-copper-tungsten alloy obtained by the preparation method has a grain size gradually refined from 10-20 μm to 10-40 nm, and the mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10%.
[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a gradient structure nickel-copper-tungsten alloy, characterized in that: Electrochemical deposition technology is adopted, nickel is used as a consumable anode, titanium, copper, copper alloy, steel or nickel is used as a cathode, and a computer is used to control the change of current density and concentration of additives in the electroplating solution over time, and a gradient structure nickel-copper-tungsten ternary alloy having both a chemical composition gradient and a grain size gradient is deposited under the action of direct current; the additives include copper salt, tungstate, citric acid or citrate, and sodium saccharin; The tungstate is sodium tungstate or ammonium tungstate, and the concentration of the tungstate increases from 0 g / L to 5-20 g / L; The concentration of the tungstate is kept constant at 0 g / L within 1-1.5 hours at the beginning of electrochemical deposition, adjusted to 2.5-10 g / L within the next 2-2.5 hours, and then adjusted to 5-20 g / L within the next 4-4.5 hours, and then kept constant within the next 0.25-0.5 hours, and the deposition is completed; The pH of the electroplating solution is 4.8-5.2, the temperature of the electroplating solution is 50-75° C., and the temperature adjustment process of the electroplating solution is: Stage a: The temperature of the electroplating solution is 70-75°C within 1-1.5 hours after the start of electrochemical deposition; Stage b: From the end of stage a to the end of deposition, the temperature of the electroplating solution is maintained at 50-56°C.
2. The method for preparing the gradient structure nickel-copper-tungsten alloy according to claim 1, characterized in that: The current density is 20-100 mA / cm 2 .
3. The method for preparing the gradient structure nickel-copper-tungsten alloy according to claim 1, characterized in that: The copper salt is copper sulfate, and the concentration of the copper sulfate gradually increases from 0 g / L to 2-10 g / L.
4. The method for preparing the gradient structure nickel-copper-tungsten alloy according to claim 3, characterized in that: The concentration of copper sulfate is kept constant at 0 g / L within 1-1.5 h after the start of electrochemical deposition, adjusted to 0.8-2.5 g / L within the next 2-2.5 h, then adjusted to 2-10 g / L within the next 4-4.5 h, and then kept constant within the next 0.25-0.5 h, and the deposition is completed.
5. The method for preparing the gradient structure nickel-copper-tungsten alloy according to claim 1, characterized in that: The citric acid or citrate is citric acid, sodium citrate dihydrate or sodium citrate pentahydrate, and the concentration of the citric acid or citrate increases from 0 mol / L to 0.2-0.6 mol / L.
6. The method for preparing the gradient structure nickel-copper-tungsten alloy according to claim 5, characterized in that: The concentration of the citric acid or citrate is kept constant at 0 mol / L within 1-1.5 hours at the beginning of electrochemical deposition, adjusted to 0.1-0.2 mol / L within the next 2-2.5 hours, and then adjusted to 0.2-0.6 mol / L within the next 4-4.5 hours, and then kept constant within the next 0.25-0.5 hours, and the deposition is completed.
7. The method for preparing the gradient structure nickel-copper-tungsten alloy according to claim 1, characterized in that: The concentration of saccharin sodium is increased from 0-5 g / L to 10-15 g / L.
8. The method for preparing a gradient structure nickel-copper-tungsten alloy according to claim 7, characterized in that: The concentration of sodium saccharin is adjusted to 0-5 g / L within 1-1.5 h after the start of electrochemical deposition, then to 5-7.5 g / L within 2-2.5 h, then to 10-15 g / L within 4-4.5 h, and then kept unchanged within 0.25-0.5 h, and the deposition is completed.
9. The method for preparing a gradient structure nickel-copper-tungsten alloy according to any one of claims 1 to 8, characterized in that: The method also includes preparing an electroplating solution before performing electrochemical deposition. The electroplating solution includes the following components: nickel sulfate hexahydrate at a concentration of 10-60 g / L, sodium bromide at a concentration of 10-20 g / L, boric acid at a concentration of 10-20 g / L, sodium tetraborate decahydrate at a concentration of 10-40 g / L, potassium sodium tartrate at a concentration of 2-10 g / L, and sodium dodecylbenzene sulfonate at a concentration of 0.3-0.6 g / L.
10. A gradient structure nickel-copper-tungsten alloy prepared by the preparation method according to any one of claims 1 to 9.
11. The gradient structure nickel-copper-tungsten alloy according to claim 10, characterized in that: The grain size of the nickel-copper-tungsten alloy is gradually refined from 10-20 μm to 10-40 nm.
12. The gradient structure nickel-copper-tungsten alloy according to claim 10, characterized in that: The mass percentages of copper and tungsten in the nickel-copper-tungsten alloy are 5-20% and 1-10% respectively.
Citation Information
Patent Citations
Grain-scale gradient metallic nickel and controllable preparation method thereof
CN104862748B
A method for preparing Ni-WP gradient alloys
CN107268046B
A gradient structure nickel-tungsten alloy, its preparation method and novel layered structure
CN111254467B
Gradient-structured nickel and tungsten alloy, preparation method and novel layered structure
CN111254467A
Preparation method of nickel-copper-phosphorus alloy with gradient structure and product of nickel-copper-phosphorus alloy
CN115233258A